2013
DOI: 10.1074/jbc.m113.468959
|View full text |Cite
|
Sign up to set email alerts
|

COP9 Signalosome Subunit Csn8 Is Involved in Maintaining Proper Duration of the G1 Phase

Abstract: Background: Among the eight subunits of the COP9 signalosome (CSN), Csn8 is only present in higher eukaryotes. Results: Decreases in Csn8 accelerate cell growth and shorten G 1 duration, whereas decreases in Csn5 impair cell proliferation. Conclusion: Although Csn5 promotes cell proliferation, Csn8 negatively regulates G 1 progression. Significance: The dynamics of CSN are an important factor influencing cell division and differentiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 61 publications
2
22
0
Order By: Relevance
“…Human Csn5 is a multitasking molecule, interacting with many important cellular regulators and harbouring metalloprotease activity. This subfraction has been shown in mammalian cells and could be either a single protein or attached to a smaller complex [34][35][36]. This subfraction has been shown in mammalian cells and could be either a single protein or attached to a smaller complex [34][35][36].…”
Section: Rpn11 and Csn5: Moonlighting Proteins At The Centre Of Pleiomentioning
confidence: 83%
See 2 more Smart Citations
“…Human Csn5 is a multitasking molecule, interacting with many important cellular regulators and harbouring metalloprotease activity. This subfraction has been shown in mammalian cells and could be either a single protein or attached to a smaller complex [34][35][36]. This subfraction has been shown in mammalian cells and could be either a single protein or attached to a smaller complex [34][35][36].…”
Section: Rpn11 and Csn5: Moonlighting Proteins At The Centre Of Pleiomentioning
confidence: 83%
“…Csn5 was initially found independently of the CSN complex, and was termed Jab1 (c-Jun activating domain-binding protein 1) [37]. Jab1 also promotes cell proliferation and its deficiency causes apoptosis or aging in mammals [34,36]. Jab1 also promotes cell proliferation and its deficiency causes apoptosis or aging in mammals [34,36].…”
Section: Rpn11 and Csn5: Moonlighting Proteins At The Centre Of Pleiomentioning
confidence: 99%
See 1 more Smart Citation
“…The peripheral association of CSN5 with the complex is dynamic since free/monomeric CSN5 is a feature found in different organisms. However, evidence suggests that free CSN5 is essentially catalytically inactive [ 11 , 26 , 29 , 36 , 37 , 38 , 39 ]. Nonetheless, one cannot rule out an as yet to be identified non-catalytic role for free CSN5 in the cell.…”
Section: Introductionmentioning
confidence: 99%
“…The highly conserved CSN2 is also important for cullin deneddylation activity of the CSN complex, and a shorter isoform, named Alien , is involved in nucleosome formation and repression of certain nuclear receptors ( Yang et al 2002 ; Eckey et al 2007 ). CSN3, CSNAP and CSN8 are in relation extremely flexible and the latter one for lower eukaryotes even assumed to be lost ( Liu et al 2013 ), which we think is questionable, as we clearly identified CSN8 homologs in, for example, Naegleria gruberi or Acanthamoeba castellanii ( fig. 1 ).…”
Section: Resultsmentioning
confidence: 81%